2017
DOI: 10.1097/shk.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metformin Use on Lactate Kinetics in Patients with Severe Sepsis and Septic Shock

Abstract: Lactate levels in metformin users were initially elevated in the early phase of resuscitation from severe sepsis and septic shock. However, there was no significant difference in lactate levels, LC, and normalization over the initial 24 h period based on metformin use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
7
37
0
Order By: Relevance
“…The acidification is due to proton accumulation rather than lactate accumulation. Lastly, it should be noted that sepsis does not alter lactate kinetics in metformin‐treated patients …”
Section: The Relationship Between Metformin and Lactic Acidosis/a Phymentioning
confidence: 98%
“…The acidification is due to proton accumulation rather than lactate accumulation. Lastly, it should be noted that sepsis does not alter lactate kinetics in metformin‐treated patients …”
Section: The Relationship Between Metformin and Lactic Acidosis/a Phymentioning
confidence: 98%
“…26 Other studies show no differences in the clearance and normalization (over 24 h) of serum lactate between sepsis patients on chronic metformin therapy and those who have not taken metformin. 31 In light of these findings, an expansion of metformin's role in sepsis may be expected. FIGURE 1 Effect of metformin in tuberculosis patients with diabetes mellitus as comorbidity.…”
Section: Sepsis Metformin and Lactatementioning
confidence: 99%
“…In fact, some studies show a lower mortality risk in sepsis patients on chronic metformin therapy compared to those not on the therapy . Other studies show no differences in the clearance and normalization (over 24 h) of serum lactate between sepsis patients on chronic metformin therapy and those who have not taken metformin . In light of these findings, an expansion of metformin's role in sepsis may be expected.…”
Section: Sepsismentioning
confidence: 99%
“…However, recent studies indicate that patents with prior use of metformin have shown nearly 30% increase survival despite high level of lactate [108]. Notably, while lactate is among well-established predictors of sepsis, recent clinical trials have shown that decrease in lactate production had no effects on sepsis survival [109110].…”
Section: Extension Of Metabolic Profile To Diagnose Outcome Of Sepsismentioning
confidence: 99%